Efektivitas Pembelajaran Outdoor Learning Process Terhadap Peningkatan Kerja Sama, Motivasi Belajar, dan Hasil Belajar IPS Siswa Sekolah Dasar - Setiawati, Esti; Wijayanti, Palupi Sri; Rianto, Rianto; Sukasih, Sukasih (Jurnal Paedagogy, 2023)
This study aims to analyze the effectiveness of implementing the outdoor learning process (OLP) learning model on cooperation, learning motivation, and social studies learning outcomes for elementary school students. This research method used experimental research with pretest and posttest designs. The subjects of this study were 15 fifth-grade students from SD Negeri Kalirejo. A test was used as the research instrument, and the results were analyzed using a paired sample test. The results of the study showed that 1) the use of the Outdoor Learning Process (OLP) learning model was effective in increasing student cooperation, indicated by increased cooperation from 26.67% before treatment and 80% after treatment; 2) the use of the Outdoor Learning Process (OLP) learning model was effective in increasing student learning motivation; this is indicated by an increase in learning motivation of 33.33% before treatment and 80% after treatment; 3) the use of the Outdoor Learning Process (OLP) learning model was effective in increasing social studies learning outcomes for students; this was shown by students who complete learning 67% before treatment and increased 93% after treatment. The pretest and posttest analysis results using the paired sample t-test show a p-value <0.05, indicating that the outdoor learning process method effectively improves social studies learning outcomes.